Pengaruh Perbandingan Konsentrasi Polimer terhadap Karakteristik dan Laju Pelepasan Patch Transdermal Nifedipin: The Effect of Comparison Polymer Concentrations on the Characteristics and Release Rate of the Transdermal Nifedipin Patch - Nur Azizah Syahrana; Surya Ningsi; Haeria Haeria; Isriany Ismail (Fakultas Farmasi, Universitas Mulawarman, Samarinda, Indonesia, 2021)
Nifedipine is a dihydropyridine anti-hypertensive drug as a calcium channel blocker with low oral biovaibility and a short half-life resulting in frequent repeated daily use of the drug when given orally in conventional dosage forms. The matrix system transdermal patch is an option that allows controlled delivery of the drug through the skin and provides patient comfort. The purpose of this study was to determine the effect of polymer deposition on the material and the in-vitro release rate of nifedipine transdermal patches with the polymer ratio of Ethyl Cellulose (EC) and Hydroxy Propyl Methyl Cellulose (HPMC) used, namely F1 (7:3), F2 (8:2) and F3 (9:1). The results of the nifedipine patch test on organoleptic examination are round, characteristic odor, yellow color and smooth surface texture. In vitro release showed that the best polymer was found in Formula 2 EC: HPMC (8:2) with good characteristics and the highest flux value was 1.307 (µg.cm-2 min-1).